Gelatin Methacryloyl Bioadhesive Improves Survival and Reduces Scar Burden in a Mouse Model of Myocardial Infarction. Issue 11 (2nd June 2020) - Ptaszek, Leon M.; Portillo Lara, Roberto; Shirzaei Sani, Ehsan; Xiao, Chunyang; Roh, Jason; Yu, Xuejing; Ledesma, Pablo A.; Hsiang Yu, Chu; Annabi, Nasim; Ruskin, Jeremy N.
Abstract : Background: Delivery of hydrogels to the heart is a promising strategy for mitigating the detrimental impact of myocardial infarction (MI). Challenges associated with the in vivo delivery of currently available hydrogels have limited clinical translation of this technology. Gelatin methacryloyl (GelMA) bioadhesive hydrogel could address many of the limitations of available hydrogels. The goal of this proof‐of‐concept study was to evaluate the cardioprotective potential of GelMA in a mouse model of MI. Methods and Results: The physical properties of GelMA bioadhesive hydrogel were optimized in vitro. Impact of GelMA bioadhesive hydrogel on post‐MI recovery was then assessed in vivo. In 20 mice, GelMA bioadhesive hydrogel was applied to the epicardial surface of the heart at the time of experimental MI. An additional 20 mice underwent MI but received no GelMA bioadhesive hydrogel. Survival rates were compared for GelMA‐treated and untreated mice. Left ventricular function was assessed 3 weeks after experimental MI with transthoracic echocardiography. Left ventricular scar burden was measured with postmortem morphometric analysis. Survival rates at 3 weeks post‐MI were 89% for GelMA‐treated mice and 50% for untreated mice ( P =0.011). Left ventricular contractile function was better in GelMA‐treated than untreated mice (fractional shortening 37% versus 26%, P <0.001). Average scar burden in GelMA‐treated mice was lower than in untreated mice (6% versus 22%, P =0.017). Conclusions: Epicardial GelMA bioadhesive application at the time of experimental MI was performed safely and was associated with significantly improved post‐MI survival compared with control animals. In addition, GelMA treatment was associated with significantly better preservation of left ventricular function and reduced scar burden.